IDENTIFICATION OF ETHNOSCIENCE DADIAH (BUFFALO MILK YOGURT) LAMBAH, SIANOK CANYON, BUKITTINGGI AS TYPICAL CULINARY OF WEST SUMATRA - Rehan ramadhani (Pendidikan IPA, FMIPA, UNP, 2021)
This study aims to look at the ethnosains in the process of making and utilizing dadiah as a traditional food in West Sumatra. This dadiah is a typical food of West Sumatra that uses the characteristics of bamboo as a medium in fermented buffalo milk. It is the powder on bamboo that helps ferment buffalo milk. The bamboo used for making dadiah is bamboo which is often referred to by the local community as